Individual and community level factors for modern contraceptives utilization among reproductive aged women in Amhara region, Mixed effect multi-level modeling, Data from Mini-EDHS, 2019 - Fassikaw Kebede Bizuneh; Tsehay Kebede Bizuneh; Seteamlak Adane Masresha; Berihun Mulu Yayeh (BMC, 2023)
Abstract Background Modern contraceptive has been identified as a key strategy to control unintended pregnancy, protect the health of the mother and child, and promote women wellbeing. Despite this and increasingly wider availability of modern contraceptives, however, there are still high levels of unmet need for birth interspacing and contraceptive use in Amhara regions. This study aimed to identify factors associated with the enhancing of modern contraceptives utilization among reproductive aged women in Amhara region, using a mixed effects multilevel modeling data from mini-EDHS 2019. Methods A community-based cross-sectional study was conducted among 711(wt = 100%) samples of reproductive-aged women. The data were interviewed by trained data collectors using a semi-structured questionnaire for the final mini-EDHS 2019 data set. A multilevel binary logistic regression model was fitted to identify the enhancing factors for modern contraceptive utilization Adjusted Odds Ratio (AOR) with 95% Confidence Intervals (CI) was used to identify factors associated with utilization. Result The median age of the participants was 31 with (IQR ± 13) years. The overall modern contraceptive utilization was 42.3% (95%CI: 38.7; 46.1). Individual and community factors accounted for 21.4% of the variation in modern contraceptive utilization at the cluster level. Being age 25 years (AOR = 12.99; 95%CI: 4.5-37.2), 26-35 years (AOR = 8.8, 95%CI: 3.25- 24), 36-45 years (AOR = 5.6, 95%CI: 2.2-16.2), being married (AOR = 4.2, 95%CI: 2.21-6.97), educated women (AOR = 11.6, 95%CI: 3.22-40.4), and being middle-economic class (AOR = 3.03; 95%CI: 1.87-4.91) were identified as individual enhancing factors. Whereas, being urban resident (AOR = 5.19; 95%CI: 5.19: 41.7) and having media exposure (AOR = 1.5; 95%CI: 1.58-3.7) were community-level enhancing factors for modern contraceptive utilization. Conclusion Compared to earlier studies, in Amhara region, a lower prevalence rate of modern contraceptive utilization was reported. The variation in utilization at the cluster level, 21.4%, was attributed to individual and community-level factors. Healthcare providers should prioritize raising awareness about contraceptive side effects to encourage new users and decrease the number of individuals who discontinue contraceptive methods.